Identity politics in Okinawan elections: the emergence of regional populism. Issue 1 (2nd January 2021) - Hijino, Ken Victor Leonard; Vogt, Gabriele
Abstract: Although identity issues have been central to Okinawan grass-roots movements, until recently few politicians have explicitly campaigned on identity appeals, rather than pacifist ideology or material promises in the form of economic development and welfare. The emergence of identity politics seeking to replace such left–right ideological competition in Okinawa appears to be a new phenomenon. Has it only been under Governor Onaga Takeshi and his 'All Okinawa' movement that identity has been used to mobilize voters in local elections? And if so, why has this new type of identity politics emerged with such force since 2014? The type of identity politics emerging under Onaga and his movement is arguably one with strong populist features, which seek to appeal to the unity of a virtuous Okinawan people against a discriminatory Japanese mainland. In Okinawa's 'regionalist populism', how are the 'people' defined and their 'will' revealed? How are the 'enemies' understood and framed? This article seeks to answer these two sets of questions concerning subnational identity politics and populism by investigating identity politics in Okinawan. To this end, the study will systematically draw upon campaign literature and speeches of local politicians, as well as deliberations and speeches in the Okinawa assembly, among other material in the post-reversion period (1972–2018). We suggest that this rising identity politics is indeed new and is born from a number of socio-economic developments, primarily an unprecedented level of distrust towards mainstream parties, the central government, and mainland Japanese among Okinawan voters.